Inhibitor of apoptosis‐stimulating p53 protein protects against inflammatory bowel disease in mice models by inhibiting the nuclear factor kappa B signaling. (7th June 2021) - Qian, Ke; Yuan, Lianwen; Wang, Shalong; Kuang, Yong; Jin, Qianqian; Long, Dongju; Jiang, Yuhong; Zhao, Hua; Liu, Kuijie; Yao, Hongliang
Summary: Drugs and therapies available for the treatment of inflammatory bowel disease (IBD) are not satisfactory. Our previous study has established the inhibitor of apoptosis‐stimulating p53 protein (iASPP) as an oncogenic regulator in colorectal cancer by forming a regulatory axis or feedback loop with miR‐124, p53, or p63. As iASPP could target and inhibit nuclear factor kappa B (NF‐κB) activation, in this study the role and mechanism of iASPP in IBD was investigated. The aberrant up‐regulation of iASPP in IBD was subsequently confirmed, based on online data sets, clinical sample examinations and 2, 4, 6‐trinitrobenzene sulfonic acid (TNBS)‐ and dextran sulfate sodium (DSS)‐induced colitis mice models. TNBS or DSS stimulation successfully induced colon shortness, body weight loss, mice colon oxidative stress and inflammation. In both types of colitis mice models, iASPP over‐expression improved, whereas iASPP knockdown aggravated TNBS or DSS stimulation‐caused colon shortness, body weight loss and mice colon oxidative stress and inflammation. Meanwhile, in both types of colitis mice models, iASPP over‐expression inhibited p65 phosphorylation and decreased the levels of tumor necrosis factor (TNF)‐α, interleukin (IL)‐1β, IL‐6, C‐X‐C motif chemokine ligand (CXCL)1 and CXCL2 in mice colons, whereas iASPP knockdown exerted opposite effects. Abstract : iASPP overexpression improved, whereas iASPP knockdown aggravated TNBS or DSS stimulation‐caused colon shortness, bodyweight loss, and mice colon oxidative stress and inflammation.